Survey of instructor and student impressions of a high‐fidelity model in canine ovariohysterectomy surgical training. Issue 6 (24th April 2019) - Au Yong, Jo Anne; Case, J. Brad; Kim, Stanley E.; Verpaalen, Valentine D.; McConkey, Marina J.
Abstract: Objective: To evaluate the usefulness of a high‐fidelity model for teaching ovariohysterectomy (OHE) to veterinary students. Study design: Longitudinal survey. Sample population: Clinicians with ≥2 years postgraduate experience in small animal surgery and a sophomore veterinary student population at 1 institution. Methods: Twelve clinicians evaluated the high‐fidelity model for realism. Questionnaires were distributed to sophomore veterinary students prior to and after OHE training on the high‐fidelity model (SynDaver Surgical Canine) and after performing OHE as primary surgeon with a live dog. Time for students to perform OHE (identify the first ovarian pedicle to transecting the uterine body) and number of technical errors (visceral injury, hemorrhage, loose ligatures) were compared between the model and live dog groups. Results: Evaluators rated the high‐fidelity model as moderate‐to‐highly realistic. Students' confidence improved after practicing on the model in all critical steps and additionally improved after performing an OHE on a live dog. Time to complete the OHE on the model (mean ± SD, 73.4 ± 27.1 minutes) and live dogs (83.0 ± 24.7 minutes) did not differ ( P = .20). Frequency of hemorrhagic events ( P = .77) and accidental visceral injury ( P = .30) did not differ between the model and live dogs. However, fewer loose ligatures were placed in live dogs (23/64) compared with the model (22/37; P = .02). Conclusion: The high‐fidelity model improved the confidence of sophomore students. The duration of OHE did not differ between the model and live dogs. Clinical impact: The high‐fidelity model is valuable for improving confidence in veterinary students prior to live‐dog OHE.